Overview Of The Tradisional The Babako Event In Marriage Nagari Jawi-Jawi Guguk, Solok Regency - Septi, Sisi Dwiana; Faridah, Anni (Universitas Negeri Padang, 2023)
Babako is a traditional Minangkabau ceremony in the form of a visit by bako to banana children. Lack of knowledge of the younger generation about the traditional Babogo, this study aims to describe the series of traditional Babogo events, types of traditional food, tools used to make traditional food and the meaning of traditional food served in the Babako traditional event in Nagari Jawi-Jawi Guguk, Solok Regency. The type of research used is qualitative research. The results of the study: 1) A series of events in Nagari Jawi-Jawi Guguk Solok Regency, including: manjapuik the bride (anak daro/marapulai), maagiah mempelai makan, manuka baju for the bride, bararak, panyarahan baban, eat basamo, go home. 2) Types of traditional food, namely: Laluak, agar-agar, rice, randang cubadak, kalio kantang dagiang, gulai cubadak, asam padeh, fried chicken, and crackers. 3) The equipment used consists of preparation tools, processing equipment, and serving tools. 4) The meaning of the traditional food served at the Babako event is as follows: silama (strengthening the relationship), agar-agar (maintaining a gentle and polite attitude), rice (purity), randang cubadak (patience and togetherness), kalio kantang dagiang (complementary to each other). ), gulai cubadak (simplicity), asam padeh (compact in running the household), fried chicken (healthy waafiat in carrying out life), crackers (customary and religious guidelines).